Three-dimensional nanoarchitectures of Co nanoparticles inlayed on N-doped macroporous carbon as bifunctional electrocatalysts for glucose fuel cells. Issue 28 (5th July 2017) - Liu, Liangzhen; Ci, Suqin; Bi, Linlin; Jia, Jingchun; Wen, Zhenhai
Abstract : Exploring high-performance electrocatalysts is of great importance for developing renewable energy conversion systems. Abstract : Exploring high-performance electrocatalysts is of great importance for developing clean and renewable energy conversion systems such as fuel cells and metal–air batteries. Hybrid nanostructures with transition metal nanoparticles embedded in a carbon matrix exhibit outstanding electrocatalytic activity and have emerged as promising low-cost alternatives to precious metal catalysts for a variety of electrochemical reactions. Herein, we report a convenient synthesis route to prepare a three-dimensional porous nanoarchitecture with Co nanoparticles (Co NPs) inlayed in nitrogen-doped macroporous carbon (Co/N-MC). The hybrids show an outstanding electrocatalytic activity for the oxygen reduction (ORR) and glucose oxidation reaction (GOR) due to the synergistic contribution of the Co NPs and nitrogen doping in macroporous carbon. Benefitting from their outstanding electrocatalytic activity in the ORR and GOR, a home-made glucose fuel cell (GFC) was set up using Co/N-MC as the anode and cathode material, delivering a considerable power density with decent stability.